Development of POE-Based Student Worksheets (Predict, Observe, And Explain) for Students' Mathematical Representation Abilities - Setiyani, Eka Nur; Baharin, Zain Hazmi Zain; Jesse, Samuel N. (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to evaluate students' worksheets for building flat-sided spaces based on POE as a learning tool in improving students' mathematical representation abilities. This research also aims to determine student and teacher responses to the use of the student worksheets that were developed. Methodology: This research uses a 4D device development method which consists of four stages, namely the definition, design, development and dissemination stages. The development stage includes validation by material experts and media experts, revision, and testing of student responses. Data collection uses student response questionnaires using student worksheets to train students' mathematical representation skills. The subjects of this research were students in class VIII of junior high school. Data analysis techniques use descriptive statistics and qualitative analysis using the Miles and Huberman model. Main Findings: The validation results of material experts and media experts show that the student worksheets developed are quite valid. This research found that the POE-based flat-sided space construction student worksheet is suitable for use in improving students' mathematical representation abilities and getting positive responses from students and teachers. This research contributes to the development of innovative and effective learning tools in the context of mathematics learning. Novelty/Originality of this study: The novelty of developing a POE-based student worksheet for students' mathematical representation abilities lies in its departure from traditional teaching methods, its emphasis on inquiry-based learning and higher-order thinking, and its adaptability to a variety of mathematical topics all contributing to a more dynamic and engaging educational experience